LAYERED HYBRID MODEL IN CRIMINAL RESOLUTION: Integrating Epkeret and State Law Under Legal Pluralism in Indonesia - Judy Marria Saimima; Adonia Ivonne Laturette; Juanrico Alfaromona Sumarezs Titahelu; Rory Jeff Akyuwen (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The ratification of the New Criminal Code (Law No. 1 of 2023) marks a paradigm shift towards restorative justice by recognizing the fulfillment of customary obligations as a valid criminal sanction. However, the absence of procedural technical guidelines creates a significant gap in the integration of customary law into the formal justice system, which could lead to legal uncertainty. This study aims to develop an operational framework using a “Layered Hybrid Model” to bridge customary criminal law and state law without violating human rights. Using sociological-legal methods and empirical data from South Buru Island, Maluku, as well as comparative analysis of customary courts in New Zealand and Canada, this study formulates a two-tiered mechanism. The first tier places customary law (Epkeret) as the primum remedium for social restoration, while the second tier establishes state law as the ultimum remedium for serious crimes. This article offers the first operational institutional design for customary criminal justice in Indonesia by proposing a State-Community Validation Forum as a constitutional filter mechanism. This model encourages a transition from weak legal pluralism to “strong and controlled legal pluralism,” ensuring that customary justice is constitutionally valid and operationally applicable in a modern criminal justice system.